Relationship of Emotional Maturity with Student Aggressive Behavior - Irma Agustina; Syahniar Syahniar; Yeni Karneli (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of the number of adolescents who tend to behave aggressively such as hitting, kicking, saying rude, mocking, fighting. Aggressive behavior is a negative behavior that is thought to be one of the contributing factors is low emotional maturity. This study aims to examine the relationship of emotional maturity with aggressive behavior. This research is a descriptive correlational type of research with quantitative methods. The sample in this study were 213 students consisting of classes X and XI. The data collection instrument was a questionnaire of emotional maturity with aggressive behavior on students using the Likert scale. Data were processed using Pearson product moment formula with the Statical Product Abd Service Solution (SPSS) program version 20.0. The results of this study reveal that there is a relationship between emotional maturity with high aggressive behavior or low emotional maturity that will affect aggressive behavior. Based on the findings of this study, it is expected that the BK counselor or counselor can provide assistance and services in the form of guidance and counseling services.